2002
DOI: 10.1124/jpet.302.2.804
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Polymorphisms of Human Organic Anion Transporters OATP-C (SLC21A6) and OATP-B (SLC21A9): Allele Frequencies in the Japanese Population and Functional Analysis

Abstract: Genetic polymorphisms of human organic anion transporting polypeptides OATP-C (SLC21A6) and OATP-B (SLC21A9) in the Japanese population were analyzed. The allele frequencies of OATP-C*1a, OATP-C*1b (N130D), OATP-C*1c (R152K and D241N), and OATP-C*5 (V174A) were 35.2, 53.7, 0, and 0.7%, respectively, in 267 healthy Japanese subjects. In the OATP-C gene, we found a novel allele called OATP-C*15 possessing two single nucleotide polymorphisms (SNPs), N130D and V174A, simultaneously. The allele frequency of OATP-C*… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
224
1
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 301 publications
(247 citation statements)
references
References 23 publications
21
224
1
1
Order By: Relevance
“…These experiments demonstrated that the K m values for estrone-3-sulfate used as model substrate are in a comparable range for all three OATP2B1 proteins. In addition, no change in the cellular distribution of all different OATP2B1 proteins could be detected (Nozawa et al 2002).…”
Section: Pharmacogenomics Of Oatp1a2 Oatp1b3 and Oatp2b1mentioning
confidence: 92%
See 2 more Smart Citations
“…These experiments demonstrated that the K m values for estrone-3-sulfate used as model substrate are in a comparable range for all three OATP2B1 proteins. In addition, no change in the cellular distribution of all different OATP2B1 proteins could be detected (Nozawa et al 2002).…”
Section: Pharmacogenomics Of Oatp1a2 Oatp1b3 and Oatp2b1mentioning
confidence: 92%
“…1), could influence the substrate spectrum whereas the mutation OATP1B1-Leu193Arg totally abolishes the transport function of the protein. Nozawa et al (2002) investigated several polymorphisms in the Japanese population and found that the previously identified OATP1B1*1c allele could not be detected in 267 healthy Japanese subjects, whereas OATP1B1*1b and OATP1B1*5 were present with 54% and 0.7%, respectively. In addition, they identified a novel allele, termed OATP1B1*15 (Table 2), possessing the two SNPs Asn130Asp and Val174Ala simultaneously.…”
Section: Pharmacogenomics Of Oatp1b1mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous study has suggested that OATP1B1 is predominantly involved in hepatic uptake of pravastatin in humans (Nakai et al 2001). Several single-nucleotide polymorphisms (SNPs) have been identified in SLCO1B1 (Nozawa et al 2002;Tirona et al 2001), and some are reported to be associated with alterations in the pharmacokinetics of certain substrate drugs, including repaglinide (Niemi et al 2005a), fexofenadine (Niemi et al 2005b), pitavastatin (Chung et al 2005;Ieiri et al 2007), and pravastatin (Mwinyi et al 2004;Niemi et al 2004;Nishizato et al 2003). Particularly subjects having SLCO1B1*15 allele (possessing both 388A [G and 521T[C) showed elevated systemic exposure of pravastatin as compared to subjects without this allele (Niemi et al 2004;Nishizato et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Very few polymorphisms of SLCO2B1 have been described [60, 61] Two rather frequent polymorphisms were initially shown to be associated with reduced transport activity of OAT2B1 for endogenous substrates (table 2), but one polymorphism was later reported to have increased drug transport activity [148,149]. Pharmacokinetically, the c.935G>A…”
Section: Oatp2b1 (Slco2b1)mentioning
confidence: 99%